Effects of prophylactic vaginal progesterone administration on mild cervical shortening (TROPICAL study): a multicenter, double-blind, randomized trial. (12th December 2022) - Hayashi, Masako; Oi, Rie; Otsuki, Katsufumi; Yoneda, Noriko; Nagamatsu, Takeshi; Kumasaka, Ryota; Miyakoshi, Kei; Aoki, Hiroaki; Tanaka, Kei; Kumazawa, Kazumasa; Ohkuchi, Akihide; Matsuda, Yoshio; et al.
Abstract: Vaginal progesterone reduces the preterm birth frequency among high-risk women with a cervical length ≤25 mm at midtrimester. However, the strategy may promote no substantial reduction in overall preterm birth rates, because such high-risk women are only approximately 2% of all pregnant women, which restrict the number of participants. Our purpose was to determine whether prophylactic vaginal progesterone administration can preserve cervical length and reduce preterm birth rates among women with mild cervical shortening. This multicenter, parallel-arm, double-blind, randomized, placebo-controlled trial involved vaginal progesterone administration (200 mg daily from 16 to 33 weeks of gestation) among asymptomatic women with a singleton pregnancy and a sonographic cervical length of 25 to <30 mm between 16 and 23 weeks of gestation. The primary and secondary endpoints were cervical shortening rates at 34 weeks of gestation and preterm birth rates, respectively. The trial was registered at the University Hospital Medical Information Network (UMIN000013518) in Japan. Between April 2014 and March 2018, 119 women were randomly assigned to the progesterone group ( n  = 59) and the placebo group ( n  = 60). No significant differences in the frequency of women with a cervical length ≥20 mm at 34 weeks of gestation were observed between both groups. All preterm births occurred after 34 weeks of gestation, except for one patient in the placebo group. The progesterone group had a lower rate of preterm birth before 37 weeks than the placebo group (3.4% vs. 15.0%, respectively; p  < .05). Despite having no effect on preserving cervical length, prophylactic vaginal progesterone administration reduced preterm birth frequency among women with mild cervical shortening. Our results are suggesting that women with mild cervical shortening are at risk for late preterm birth and the need for expanding progesterone treatment indications to include not only high-risk but also low-risk populations.